Polyphenols, oral health and disease: A review - Petti, Stefano; Scully, Crispian (Journal of dentistry, 2009)
Polyphenols (PPs) are reactive metabolites abundant in plant-derived foods, particularly fruits, seeds and leaves. In the tissues of the digestive tract, particularly the oral mucosa, active PPs reach the highest concentration. Although excessively high and monotonic intake may be toxic (such an effect is countered by salivary proline-rich proteins), PPs exert preventive activity against infectious and degenerative diseases and may also help prevent oral diseases, via mechanisms like antioxidant activity and neutralisation/modulation of human/bacterial/viral proteins/enzymes. This review seeks to investigate the preventive PP activity against oral diseases. Studies published during the last 15 years were searched using MEDLINE, PUBMED, EMBASE. The quality of evidence was rated using the three-point scale used by the US Preventive Services Task Force to assess the merits of preventive measures. Consistent, well-designed, epidemiological, animal and in vitro studies directly and indirectly support the preventive PP effect against oral cancer with good evidence. Consistent studies showing that PPs inactivate periodontal pathogens and increase antioxidant capacity of oral fluids, suggest a preventive effect against periodontal disease with fair evidence. Animal and in vitro studies showing that PPs decrease mutans streptococci virulence and dental plaque accumulation, suggest a preventive effect against dental caries with fair evidence. Meta-analysing clinical trials on subjects refraining from oral hygiene, PP-containing mouthrinses decrease mutans streptococci level by almost 50% and Plaque Index score. Regular and frequent PP intake may help protect against oral cancer, while human studies are needed to confirm the promising preventive activity against periodontal disease and caries.